KOMPARASI KESEHATAN PT BANK MANDIRI Tbk DAN PT BANK BUMI ARTA Tbk BERDASARKAN EARNINGS DAN CAPITAL PERIODE 2016-2020 - Iis Muflichah (FEB Universitas Maritim Semarang, 2022)
This study aims to determine and analyze how the health comparison of PT. Bank Mandiri (Persero) Tbk and PT Bank Bumi Arta Tbk based on earnings and capital for the 2016-2020 period. The collection technique in this research is using the documentation on financial statements and literature studies of the theories used. Sampling in the form of financial statements, income statements and balance sheets obtained from the Indonesia Stock Exchange (IDX) which is accessed on the website www.idx.The data analysis technique used is quantitative descriptive analysis. Banking soundness level based on Earnings and capital consisting of ROA, ROE, NIM BOPO, and CAR. From the results of this study indicate that the health level of PT. Bank Mandiri (Persero) Tbk is better than PT Bank Bumi Arta Tbk. This is due to differences in the level of supervision of the bank's health performance which give rise to different health management for each bank.